Revisiting Dynamic Capabilities in the Digital Era: Toward a Framework of Adaptive Strategic Resilience - Meyer, Anna Sophie Meyer; Fischer, Mateo Fischer (International Journal Business and Entrepreneurship, 2025)
The purpose of this conceptual paper is to revisit and extend the dynamic capabilities theory by integrating it with digital transformation and organisational resilience. Building on Teece’s (2007) foundational framework, this study synthesises recent literature (2018–2024) to conceptualise how sensing, seizing, and reconfiguring capabilities evolve within digitally enabled contexts. The analysis reveals that digital transformation accelerates capability renewal and enhances organisational resilience by fostering continuous learning, data-driven foresight, and adaptive reconfiguration. The paper advances the theoretical understanding that resilience is not a separate construct but an emergent outcome of dynamic processes embedded in digital ecosystems. From a managerial perspective, it highlights that digital infrastructures, leadership cognition, and ambidextrous culture are key enablers of adaptive advantage in volatile environments. This integration contributes to the redefinition of dynamic capabilities as predictive and generative mechanisms rather than reactive routines. The study concludes by proposing directions for future empirical validation, including the operationalisation of digital dynamic capabilities and resilience measures across industries.